The European Federation for Medicinal Chemistry and Chemical Biology (EFMC) Best Practice Initiative: Phenotypic Drug Discovery. (7th April 2021) - Quancard, Jean; Bach, Anders; Cox, Brian; Craft, Russell; Finsinger, Dirk; Guéret, Stéphanie M.; Hartung, Ingo V.; Laufer, Stefan; Messinger, Josef; Sbardella, Gianluca; Koolman, Hannes F.
Abstract: Phenotypic drug discovery has a long track record of delivering innovative drugs and has received renewed attention in the last few years. The promise of this approach, however, comes with several challenges that should be addressed to avoid wasting time and resources on drugs with undesired modes of action or, worse, false‐positive hits. In this set of best practices, we go over the essential steps of phenotypic drug discovery and provide guidance on how to increase the chance of success in identifying validated and relevant chemical starting points for optimization: selecting the right assay, selecting the right compound screening library and developing appropriate hit validation assays. Then, we highlight the importance of initiating studies to determine the mode of action of the identified hits early and present the current state of the art. Abstract : Don′t be afraid of the black box : Recent years have seen a renaissance of phenotypic drug discovery (PDD) with novel screening technologies and a track record thought to match or surpass that of target‐centric approaches. We present a view on best practices to consider when running PDD campaigns to increase the chance of success of these black‐box approaches.